2013
DOI: 10.7314/apjcp.2013.14.7.4319
|View full text |Cite
|
Sign up to set email alerts
|

Hookah Smoking: Characteristics, Behavior and Perceptions of Youth Smokers in Pune, India

Abstract: Background: Hookah smoking has been referred to as a global tobacco epidemic by public health officials. This study aimed to investigate the characteristics, behaviour and perceptions related to hookah smoking among the youth smokers in Pune. Methods: Two hundred and eighty established hookah smokers participated in this study. Data was collected using a 29-item questionnaire, constructed using three main domains: Characteristics (socio-demographic and personal), behaviour and perceptions (about harmful effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 18 publications
4
20
2
2
Order By: Relevance
“…However, our findings about misperceptions and the proportion of current versus ever waterpipe smokers are similar to prior studies involving university students in other parts of the U.S. and across the world (Amin et al 2010; Haider et al 2015; Heinz et al 2013; Kakodkar and Bansal 2013). Another limitation is that health warnings were presented in the same order for all subjects, which may have led to biased results (Landon 1971).…”
Section: Discussionsupporting
confidence: 87%
“…However, our findings about misperceptions and the proportion of current versus ever waterpipe smokers are similar to prior studies involving university students in other parts of the U.S. and across the world (Amin et al 2010; Haider et al 2015; Heinz et al 2013; Kakodkar and Bansal 2013). Another limitation is that health warnings were presented in the same order for all subjects, which may have led to biased results (Landon 1971).…”
Section: Discussionsupporting
confidence: 87%
“…This finding may suggest that investigators implementing prevention strategies should consider intervening on hookah use behavior during early adolescence. Finally, it is worth noting that participants in the present study largely perceived that hookah use was not as harmful to health relative to alcohol or cigarettes, a misperception that echoes previous work (Aljarrah, Ababneh, & Al- Delaimy, 2009; Kakodkar & Bansal, 2013; Martinasek, Gibson-Young, & Forrest, 2014). Such misperceptions may arise from beliefs about normative behaviors, having many friends who have tried hookah, or, based on hookah use having fewer associated restrictions, views that it is socially acceptable (Berg et al, 2015; Heinz et al, 2013).…”
Section: Discussionsupporting
confidence: 73%
“…Study done in Saudi Arabia 2007 showed that most of the students (52%) smoked for 1 to 2 days in the last 30 days and only 6% smoke every day, and most of them smoked more than 4 times a day 29.1% and 2.4% prefer to smoke more than 20 cigarettes a day (Abdalla et al, 2007) 24.6% of young hookah smokers in Pune India smoked every day (Kakodkar and Bansal, 2013). In the order of cost, Shisha is most expensive, followed by cigarettes, then Dokha.…”
Section: Discussionmentioning
confidence: 99%